Unravelling the factors decisive to the implementation of EPODE-derived community approaches targeting childhood obesity: a longitudinal, multiple case study. Issue 1 (December 2016) - van der Kleij, Maria; Crone, Mathilde; Reis, Ria; Paulussen, Theo
Abstract Background Implementation of intersectoral community approaches often fails due to a translational gap between the approach as intended and the approach as implemented in practice. Knowledge about the implementation determinants of such approaches is needed to facilitate future implementation processes. Methods The implementation of five EPODE-derived intersectoral community approaches was studied longitudinally. Semi-structured interviews were held with 189 community stakeholders from four sectors to elucidate which determinants influenced implementation, and if an to which extent determinants differed across communities, sectors and over time. A framework approach was used to analyze our data. Results Twenty-two key determinants of implementation were identified. Facilitators named were mostly proximal (stakeholder level), and barriers were mostly distal (context level). Key determinants varied greatly across sectors and over time, especially between the educational & health care sector and the private, welfare & sports sector. Only 'perceived importance of IACO goals' was identified as an universal implementation facilitator. Conclusions Striking differences in determinants were found across sectors and over time. Also, stakeholders expressed that possibilities to adapt the approach to the local context were needed to improve implementation. We therefore propose to develop sector- and time specific leads for implementation, which should be approved and amended (over time) by stakeholders. This so-called 'mutual adaptation' allows for the use of both scientific insights and practice-based knowledge, enabling program management and community stakeholders to collaboratively improve their implementation efforts.